2008
DOI: 10.1200/jco.2007.14.9021
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Follow-Up of Radiation Therapy Oncology Group Protocol 92-02: A Phase III Trial of the Duration of Elective Androgen Deprivation in Locally Advanced Prostate Cancer

Abstract: LTAD as delivered in this study for the treatment of locally advanced prostate cancer is superior to STAD for all end points except survival. A survival advantage for LTAD + RT in the treatment of locally advanced tumors with a Gleason score of 8 to 10 suggests that this should be the standard of treatment for these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
407
3
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 634 publications
(446 citation statements)
references
References 17 publications
15
407
3
15
Order By: Relevance
“…This trial demonstrated a significant increase in late Grade 3 and higher toxicity associated with RT and LTAD (p = 0.037). Grade 3 or higher GI toxicity was 10% for STAD and 25% for LTAD (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trial demonstrated a significant increase in late Grade 3 and higher toxicity associated with RT and LTAD (p = 0.037). Grade 3 or higher GI toxicity was 10% for STAD and 25% for LTAD (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of androgen deprivation (AD) therapy to 3DCRT for intermediate and highrisk prostate cancer has been shown to improve in local control, biochemical-free survival, distant metastases and overall survival (5)(6)(7)(8). Some studies have suggested that the addition of AD increases the risk of GI and GU toxicity while others have not (7,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Original Article RTOG 92-02 9 and was calibrated to result in survival estimates comparable to data in the reported literature. We assumed that the rate of metastasis as first failure was constant over the 10 years of follow-up.…”
Section: Patterns Of Failure and Mortalitymentioning
confidence: 99%
“…The optimal duration of ADT in men undergoing RT has been addressed in at least four trials, all of which suggest benefit from prolonged therapy [47,[53][54][55][56]. For example, in the largest trial, RTOG 92-02, 1,554 men with T2c-T4 disease received 4 months of goserelin and flutamide (2 months before and during EBRT) and were then randomly assigned to no further therapy or 24 months of additional goserelin.…”
Section: How Long Should Abiraterone Acetate Be Continued After Progrmentioning
confidence: 99%